Front Cover: Multi‐Mechanistic Antidiabetic Potential of Astaxanthin: An Update on Preclinical and Clinical Evidence. Issue 24 (15th December 2021) - Gowd, Vemana; Xiao, Jianbo; Wang, Mingfu; Chen, Feng; Cheng, Ka‐Wing
Abstract : Mol. Nutr. Food Res . 2021, 65, 202100252 DOI: 10.1002/mnfr.202100252 This review summarizes the connection between glucose homeostasis, oxidative stress, and diabetes mellitus, the pharmacological effects of astaxanthin against insulin resistance, diabetic retinopathy, diabetic nephropathy, and neurological damage emphasizing the cellular and molecular mechanisms involved. A few lines of clinical evidence supporting its antidiabetic potential are also highlighted. This is reported by Ka‐Wing Cheng and co‐workers in article number 2100252 .